2017
DOI: 10.1590/1517-869220172306160084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Training on the Myocardium of Female LDL Knockout Ovariectomized Mice

Abstract: Introduction: The emergence of coronary heart disease increases with menopause, physical inactivity and with dyslipidemia. It is known that physical training promotes the improvement of cardiovascular functions. Objective: The purpose of this study was to investigate the effects of aerobic physical training on the left ventricle in female LDL knockout ovariectomized mice. Methods: Thirty animals were divided into 6 groups (n=5), namely, sedentary non-ovariectomized control; sedentary ovariectomized control; tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…4 9 However, physical exercise allows a decrease in the levels of fat stored in the VAT, thus the adipocytes decrease in size. 1 20 21 Rodrigues et al 22 working with Sprague–Dawley females showed that ovariectomy increased adipocyte hypertrophy and that training decreased the area of fat cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 9 However, physical exercise allows a decrease in the levels of fat stored in the VAT, thus the adipocytes decrease in size. 1 20 21 Rodrigues et al 22 working with Sprague–Dawley females showed that ovariectomy increased adipocyte hypertrophy and that training decreased the area of fat cells.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 However, physical exercise allows a decrease in the levels of fat stored in the VAT, thus the adipocytes decrease in size. 1,20,21 Rodrigues et al 22 working with Sprague-Dawley females showed that ovariectomy increased adipocyte hypertrophy and that training decreased the area of fat cells. It is known that adipose tissue has high plasticity and maintains its ability to expand throughout the life of animals through hypertrophy and hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Such data are important for studies of the response of the bone experimental stimuli in aged rats, to distinguish the response to the stimuli from accompanying age-related changes. 12 Morphometry is a method of quantitative morphology that allows accurate determination of changes in different tissues with increasing age 7,[13][14][15][16][17][18] . The purpose of the present work was to investigate the bone density, maximum resistance force, and bone stiffness of the rat femur, as a function of growing and aging.…”
Section: Introductionmentioning
confidence: 99%